Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.6 - Derivatives of Logarithmic Functions - 3.6 Exercises - Page 223: 44


$y'=x^{cosx}(\frac{cosx}{x}-lnx sinx)$

Work Step by Step

Given: $y =x^{cos x}$ Taking logarithmic on both sides of the function $y =x^{cos x}$ $lny=cosx .lnx$ Take implicit differentiation with respect to $x$. Apply product rule of differentiation. $\frac{d}{dx}(lny)=\frac{d}{dx}(cosx. lnx)$ $\frac{1}{y}\frac{d}{dx}(y)=cosx\frac{d}{dx}(lnx)+lnx\frac{d}{dx}(cosx)$ $\frac{d}{dx}(y)=y[cosx\times(\frac{1}{x})+lnx(-sinx)]$ Hence, $y'=x^{cosx}(\frac{cosx}{x}-lnx sinx)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.